A nomenclator botanicus for the bryophyllous and related species published in, or transferred to, Bryophyllum, now included in Kalanchoe (Crassulaceae subfam. Cotyledonoideae) - Smith, Gideon F. (Phytotaxa, 2025)
From 1805, the year in which the genus name Bryophyllum was published, until 1907 / 1908 when Raymond-Hamet published the first modern monograph of Kalanchoe, Bryophyllum was sometimes accepted at the rank of genus or as a synonym of Kalanchoe. Although Augustin Pyramus de Candolle had suggested as early as in 1828 that Bryophyllum should be included in Kalanchoe, this was only done formally in Raymond-Hamet’s two-part monograph more than 70 years later. However, in 1930 Alwin Berger, when treating the Crassulaceae for the second edition of Die natürlichen Pflanzenfamilien, reinstated Bryophyllum, as well as Kitchingia, for that matter, as accepted genera. The kalanchooid taxonomy presented by Berger proved to be influential and was adopted in, for example, several regional Floras, such as those produced for Angola (Conspectus florae angolensis), the Flora zambesiaca region, the Flora of Southern Africa region, and the Flora of China (but not in the Flora of Ceylon [Sri Lanka]). The global synoptic treatment of Kalanchoe by Bernard M. Descoings published in 2003 again reverted to treating Bryophyllum at an infrageneric rank in Kalanchoe, as K. sect. Bryophyllum, so following Pierre L. Boiteau who published the latter combination in 1947, after Sijfert H. Koorders had already recognised K. subg. Bryophyllum, i.e., at the rank of subgenus, in 1919. Most recently, combinations were published in Bryophyllum in 2008, when several kalanchoes described, especially, from the late-1990s onwards, were transferred to Bryophyllum. However, Bryophyllum is at present recognised at the rank of subgenus in Kalanchoe, as K. subg. Bryophyllum, as published by Koorders. A nomenclator botanicus for Bryophyllum is presented here, along with the equivalent names under which they are at present accepted in Kalanchoe. This paper forms part of ongoing work on the taxonomy and nomenclature of Kalanchoe globally. A selection of bryophyllous kalanchoes is illustrated.